CAMPBELL MONOMYTH ANALYSIS OF SOUTH SUMATERA FOLKLORE - Hikmah Yanti, Cita; Nopriani, Siska (Universitas Muhammadiyah Palembang, 2024)
This research focuses on Campbell Monomyth’ analysis of South Sumatera folklore. The purposes of this research are to describe the intrinsic elements of each story in South Sumatera folklore and analyze how the Monomyth is present in each story of South Sumatera folklore. Monomyth theory by Joseph Campbell is used as the main theory to find out the stages of a hero’s journey or Monomyth in each of Sumatera Selatan folklore. To conduct this research, the researcher uses the descriptive qualitative method. The data sources in this research are the book entitled Kumpulan Cerita Rakyat Sumatera Selatan by Kurnianto, Nirmala & Rosita and the internet to complete the data. The researcher analyzes the data to find out the intrinsic elements and find out the presence of Monomyth theory in each of South Sumatera folklore. The result of the research shows all of the heroes in each of South Sumatera folklore completed all the sections of the hero’s journey or Monomyth; Departure, Initiation, and Return except the hero in the folklore of Raden Keling who only completed the sections Departure and Initiation. The missing section occurred because of the cultural difference. Therefore, South Sumatera folklore goes through the same stages as the stages of the hero’s journey or Monomyth.